2015
DOI: 10.1016/j.sbspro.2015.01.756
|View full text |Cite
|
Sign up to set email alerts
|

Reading Comprehension Intervention Program for Teachers from 3rd Grade’ Students

Abstract: This study aimed to verify the effectiveness of Reading comprehension intervention program for teachers from 3rd grade'students. 4 teachers of 3rd grade from public school were divided: GI -two teachers submitted to intervention program and GII -two teachers not submitted to intervention program. Reading Comprehension Assessment Protocol was applied in all students of these teachers in pre and post-intervention. The results revealed a difference between the performance of the situations of pre and post-testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
1
5
0
4
Order By: Relevance
“…Our results corroborate those found by Wilawan (2011) and Sánchez et al (2012), who reported effects of an explicit instructional procedure on main idea comprehension (incorporating selection, generalization, and integration macrorules) and the knowledge of the thematic progression and basic structural organization. The GIII (5th grade) results obtained in the present study are in agreement with those reported in the aforementioned studies, which showed that the students submitted to the program training had better performance on the expository texts.…”
Section: Discussionsupporting
confidence: 92%
“…Our results corroborate those found by Wilawan (2011) and Sánchez et al (2012), who reported effects of an explicit instructional procedure on main idea comprehension (incorporating selection, generalization, and integration macrorules) and the knowledge of the thematic progression and basic structural organization. The GIII (5th grade) results obtained in the present study are in agreement with those reported in the aforementioned studies, which showed that the students submitted to the program training had better performance on the expository texts.…”
Section: Discussionsupporting
confidence: 92%
“…Readers Theatre (Myrset [19]) is another way role play can be used in the classroom for students to practice oral interpretation, expression, vocabulary development, and overall reading comprehension, as well as improve fluency. Capellini, Pinto & Cunha [20] states that role play in teaching and learning genre could improve students' comprehension. Vaish also [21] found improved self-concept after using role play to improve reading comprehension.…”
Section: Role Play In Reading Comprehensionmentioning
confidence: 99%
“…Outras investigações comparam a compreensão leitora em textos narrativos e expositivos (e.g., BARETA et al, 2009;BAŞTUĞ, 2014;CADIME et al, 2017;CAPELLINI, 2015;ÇAKIR, 2008;MCNAMARA, OZURU;FLOYD, 2011;WOLFE, 2005). Baştuğ (2014), por exemplo, comparou, por meio do teste de Cloze, as habilidades de compreensão de leitura em alunos de 4º e 5º anos, observando que os participantes tinham um melhor desempenho no texto narrativo que no expositivo.…”
Section: Introductionunclassified